The impact of endovascular stents types on perioperative outcomes of ruptured abdominal aortic aneurysms: a single-center experience - Ma, Huibo; Wang, Xueyi; Liu, Yangshuo; Li, Yongxin; Guo, Mingjin (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Ruptured abdominal aortic aneurysm (rAAA) represents a critically urgent vascular surgical condition, and endovascular aneurysm repair (EVAR) is a clinically effective treatment option. This study aims to investigate whether the type of intravascular graft used for ruptured abdominal aortic aneurysms has an impact on perioperative outcomes of EVAR. Methods: A retrospective analysis was conducted on patients who underwent EVAR for ruptured abdominal aortic aneurysm at a single medical center from 2019 to 2022. Patients who required simultaneous stent implantation in the renal arteries or visceral arteries, as well as those with ruptured aneurysms located in the para-renal, supra-renal, or thoracoabdominal regions, were excluded from the analysis. Additionally, patients who underwent open surgery during the initial procedure or converted to open repair were excluded. The primary endpoint was perioperative mortality rate. Other study outcomes included perioperative complications, reoperation rates, and length of hospital stay. Characteristics and corresponding outcomes of patients receiving different endovascular stent treatments were compared using SPSS software. Results: A total of 58 patients received treatment with two types of endovascular stents: Gore Excluder (n=29) and Microport Hercules (n=29). The number of other endografts was too small for statistical analysis. Compared to patients treated with Hercules, those treated with Excluder had a significantly increased likelihood of concomitant coronary atherosclerosis (P=0.009) and potentially higher creatinine levels (P=0.014). Additionally, Excluder was more commonly used in patients with shorter aneurysm necks (P<0.001). There was a statistically significant difference in overall mortality between the two groups (Hercules 27.6%, Excluder 6.9%, P=0.037). Furthermore, patients who received Excluder treatment had lower mortality rates in subgroups of non-alcohol users (P=0.028), non-diabetic patients (P=0.027), and patients with dispersed thrombosis at the proximal neck (P=0.046). In the multivariate analysis, the type of stent used and the occurrence of intraoperative complications in patients with rAAA was identified as an independent risk factor for perioperative mortality. Conclusion: Our study suggests that the management of intraoperative complications may be a modifiable factor that can improve outcomes. Patients receiving Excluder treatment demonstrated better performance in EVAR for single-center rAAA patients compared to other endovascular stents, and this difference warrants further investigation.